Influence of integrated nutrient management practices on productivity and economics of soybean-safflower cropping system on vertisols of Marathwada region: INFLUENCE OF INM ON PRODUCTIVITY AND ECONOMICS OF SOYBEAN-SAFFLOWER CROPPING SYSTEM - G M KOTE; S B GHUGE; C B PATIL; S A SHINDE (Journal of Oilseeds Research, 2016)
An experiment on soybean-safflower cropping systemconsisting offour main treatments for soybean viz., 100% recommended dose of fertilizer (RDF), 50% RDF + 3.5 t/ha safflower residues, 50% RDF + 2.5 t/ha FYM + 3.5 t/ha safflower residues and 5 t FYM/ha + 3.5 t/ha safflower along and five sub plot treatments for safflower viz., 100% RDF, 50% RDF + 6 t FYM/ha, 50% RDF + 3 t/ha soybean residues/ha, 50% RDF + 3 t FYM/ha + 3 t soybean residues/ha and 6 t FYM/ha+ 3 t soybean residues/ha was conducted at research farm of AICRP on Safflower, VNMKV, Parbhani during kharif and rabi seasons of 2010-11 to 2013-14. The results showed that application of 100% RDF and 50% RDF + 2.5 t FYM/ha + 3.5 t safflower/ha residues to soybean were at par and recorded significantly higher safflower equivalent yield, gross monetary returns and net monetary returns than other treatments. Further, application of 100% NPK was found to have given significantlysafflower equivalent yield, gross monetary returns and net monetary returns besides B:C ratio. Next best treatment was application 50% NPK + 3t/ha FYM + 3t/ha soybean residues to soybean.